On Track for a Truly Green Propolis-Fingerprinting Propolis Samples from Seven Countries by Means of a Fully Green Approach - Funari, Cristiano Soleo [UNESP]; Carneiro, Renato Lajarim; Creese, Mari Egeness; Leme, Gabriel Mazzi [UNESP]; Cavalheiro, Alberto José [UNESP]; Hilder, Emily Frances (American Chemical Society (ACS), 2016)
The production of quality bee products, as well as bee survival itself, depends on the health conditions of the environment, but ironically, harmful solvents are often employed by scientists and traders to monitor the quality of these products. Many types of propolis have been recognized around the world, but specific biological activities can be expected for specific types of propolis. This work aimed to develop a new and green ultrahigh performance liquid chromatography method for the identification of green propolis type. The method was able to discern this type of propolis in a set of samples from seven countries as well as to cluster these samples by fingerprint similarity based on principal component analysis and partial least squares-discriminant analysis. This proved to be efficient, reproducible, and greener than methods previously reported in the literature for similar purposes and compatible with the cheap, largely available food grade ethanol produced from sugar cane
Keywords: Bioethanol; Green chemistry; Green chromatography; Green solvents; Metabolite profiling